Environmental niche conservatism explains the accumulation of species richness in Mediterranean‐hotspot plant genera. (2nd February 2017) - Skeels, Alexander; Cardillo, Marcel
Abstract : The causes of exceptionally high plant diversity in Mediterranean‐climate biodiversity hotspots are not fully understood. We asked whether a mechanism similar to the tropical niche conservatism hypothesis could explain the diversity of four large genera ( Protea, Moraea, Banksia, and Hakea ) with distributions within and adjacent to the Greater Cape Floristic Region (South Africa) or the Southwest Floristic Region (Australia). Using phylogenetic and spatial data we estimated the environmental niche of each species, and reconstructed the mode and dynamics of niche evolution, and the geographic history, of each genus. For three genera, there were strong positive relationships between the diversity of clades within a region and their inferred length of occupation of that region. Within genera, there was evidence for strong evolutionary constraint on niche axes associated with climatic seasonality and aridity, with different niche optima for hotspot and nonhotspot clades. Evolutionary transitions away from hotspots were associated with increases in niche breadth and elevated rates of niche evolution. Our results point to a process of "hotspot niche conservatism" whereby the accumulation of plant diversity in Mediterranean‐type ecosystems results from longer time for speciation, with dispersal away from hotspots limited by narrow and phylogenetically conserved environmental niches.